Cooperative organizations as an engine of equitable rural economic development. Issue 1 (June 2015) - Altman, Morris
Abstract: Cooperatives represent an alternative to large-scale corporate farms as well as to independent unaffiliated small private farms. This article presents a comparative modeling narrative on cooperative organizational forms' potential impact on equitable rural development. This speaks to issues of both increasing the size of the economic pie and how this income is distributed. The case is made that cooperatives can potentially generate higher rates of growth and more equitable growth, even in competitive economic environments. An important type of cooperative that is focused upon is one based on the linking of smaller farms into a cooperative. Economies of scale and scope as well in transaction costs can be captured by the cooperatives. Given cooperative governance, one would also expect higher levels of x-efficiency. Overall, cooperatives can generate relative high incomes to cooperative members, whilst remaining competitive with the traditional privately owned large farms. Critical to the success of the cooperative is a set rules and regulation that place them on a level playing field with the privately owned farm. In addition, the implementation and practice of cooperative principles are key to the success of the cooperative farm.